Chemistry and hygiene of food gases - Laganà, Pasqualina; Campanella, Giovanni; Patanè, Paolo; Assunta Cava, Maria; Parisi, Salvatore; Gambuzza, Maria Elsa; Delia, Santi; Coniglio, M. A. (SpringerBriefs in molecular science., 2019)
This book focuses on the use of food gases in the food industry, their different applications and their role in food processing, packaging and transportation. Since these gases come into contact with food, they must comply with strict of labeling, purity and hygiene standards in order to ensure food safety. The book discusses various implications of food gases in the food chain, providing examples of how they can be used to limit food waste and losses. The first two chapters examine the classification and role of food gases in Europe, and the third chapter then explores the chemical and physical features of commonly used food gases in the food and food packing industries. The fourth chapter highlights the impact of food gases on human health due to their possible abuse and misuse. This book appeals to researchers and professionals working in food production and quality control.